Youth Transitions among Descendants of Turkish Immigrants in Amsterdam and Strasbourg: A Generation in Transition - Keskiner, Elif (IMISCOE Research Series,, 2019)
This open access book maps the youth transitions of descendants of migrants from Turkey living in Amsterdam and Strasbourg, through a comparative mixed-methods research design. As such, it is of interest to discussions in youth sociology, social mobility and second-generation research. The book follows transition trajectories of the second-generation, from school to activity or inactivity in the labour market, to marriage or further study and, deepens our understanding of transitions by unravelling the macro and micro mechanisms behind individual pathways. On the one hand, the author reveals the ongoing significance of distinct macro institutional settings as well as social structures such as social class, ethnicity and gender in shaping the youth transition experience. On the other, she shows that youth transitions are not predestined to social reproduction when institutional and social structures create conditions for the development of resources necessary for social mobility. Therefore, through an examination of how immigrants' descendants develop forms of capital in their social trajectories, in relation to institutional and social structures, the book advances the theoretical discussion on Bourdieu's capital theory. Moreover, in times when native-born descendants of immigrants are at the forefront of public debate being subjected to normative integration demands, the book significantly shifts the lens and draws our attention to the daily challenges and realities faced by ethnic minority youth.